Tabayyun as an Anti-Cyberbullying Educational Paradigm: A Tafsir Tarbawi Perspective on Surah Al-Ḥujurāt Verse 6 in Islamic Digital Literacy - Nurwahida Nurwahida; Abdurrahman Gatteng; St. Wardah Hanafie Das; Mahsyar Idris; Mowafg Masuwd (ZAD Al-Mufassirin, 2026)
This study is motivated by the increasing phenomenon of cyberbullying in the digital era, which is influenced by weak information verification practices, low critical literacy, and the lack of digital communication ethics among students. This study aims to analyze the concept of tabayyun in QS. Al-Ḥujurāt verse 6 from the perspective of tafsir tarbawi and its relevance as an anti-cyberbullying educational paradigm within Islamic digital literacy. The research employed a qualitative approach based on library research using content analysis methods on the Tafsir of Ibn Kathir, As-Sa‘di, and Al-Munir by Wahbah Az-Zuhaili. Data were analyzed through thematic coding, categorization, and interpretative triangulation. The findings reveal that tabayyun contains epistemological, moral, pedagogical, and social dimensions, including information verification, prudence, source validity, avoidance of hasty judgment, and social responsibility in digital communication. The study also indicates that weak implementation of tabayyun is associated with the spread of hoaxes, disinformation, digital impulsivity, and aggressive behavior on social media, which may increase the risk  of cyberbullying. The novelty of this study lies in reconstructing tabayyun as an anti-cyberbullying educational paradigm based on tafsir tarbawi, integrating cognitive, affective, and behavioral dimensions within Islamic digital literacy. The implications of this research highlight the importance of integrating the values of tabayyun into Islamic education to develop a critical, ethical, and humanistic digital culture.